Inkjet-printed embedded Ag-PEDOT:PSS electrodes with improved light out coupling effects for highly efficient ITO-free blue polymer light emitting diodes - Kinner, Lukas; Nau, Sebastian; Popovic, Karl; Sax, Stefan; Burgués-Ceballos, Ignasi; Hermerschmidt, Felix; Lange, Alexander; Boeffel, Christine; Choulis, Stelios A.; List-Kratochvil, E.J.W. (My University, 2017)
We report on solution processed polymer light emitting diodes (PLEDs) using inkjet-printed embedded and non-embedded metal grid anodes. Metal grids were inkjet-printed in a honeycomb layout. Honeycomb dimensions were varied from 3 mm to 8 mm to optimize device performance. Inkjet-printed grids were then coated with a highly conductive PEDOT:PSS formulation. First experiments on PEDOT:PSS coated, non-embedded metal grid anodes showed that grids with a 3 mm honeycomb diameter have a similar efficiency as optimized indium tin oxide (ITO) based reference devices. To further improve the efficiency of the devices, the honeycomb Ag-grids were embedded in an Ormocer®-based material. A detailed performance analysis of PLEDs fabricated on ITO, non-embedded and embedded grids was carried out. It is shown that reduced leakage current and enhanced light outcoupling by embedding result in a significant efficiency enhancement of 250% in inkjet-printed embedded Ag-PEDOT:PSS ITO-free PLEDs, compared to the ITO-based reference PLEDs.
Keywords: Anodes; Electrodes; Light emitting diodes; Plastic coatings; Tin oxides